PENGARUH MASA PERIKATAN AUDIT, BIAYA AUDIT DAN UKURAN KAP TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Nayla Meutia Nanditta; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This research aims to analyze the effect of audit tenure, audit fee, and audit firm size on financial statement fraud. The dependent variable is financial statement fraud. The independent variables in this study are audit tenure, audit fee, and audit firm size. This study uses a quantitative approach with secondary data obtained from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) during the observation period of 2022–2024. The population in this study consists of all manufacturing sector companies, totaling 39 firms. The sampling technique used is purposive sampling based on certain criteria. The data analysis method employed is multiple linear regression using SPSS software. The research findings indicate that audit tenure has a positive effect on financial statement fraud. This implies that a longer audit tenure leads to a higher indication of financial statement fraud. Additionally, audit fees have a significant negative effect on financial statement fraud, meaning that higher audit fees are associated with a lower likelihood of fraudulent financial reporting. The audit firm size variable does not have a significant effect on financial statement fraud. This suggests that both Big Four and Non-Big Four audit firms possess the same quality of financial reporting capability.